Characteristics, distribution, and origin of ferruginous deposits within the Late Ordovician glaciogenic setting of Arabia - Abdullah Alqubalee; Anas Muhammad Salisu; Abdulwahab Muhammad Bello; Abdulkarim Al-Hussaini; Khalid Al-Ramadan (Scientific Reports, 2023)
Abstract Ferruginous deposits are iron-rich sediments or sedimentary rocks found in various sizes, shapes, and compositions within sedimentary strata in different depositional settings. This study investigates the characteristics, distribution, and origin of ferruginous deposits found in the Late Ordovician glaciogenic Sarah Formation and surrounding deposits in central Saudi Arabia. Several types of ferruginous deposits have been identified through field observations and laboratory investigations, including thin-section petrography, geochemical, surface, and bulk mineralogical analyses, and computed tomography scans. The identified ferruginous deposits include solid and rinded concretions, pipes, layers, ferricretes, liesegang bands, and fracture infills. They were associated with the periglacial and proglacial facies of the Sarah Formation. For instance, ferruginous deformed layers were mainly observed in subglacial facies, while rinded concretions occurred in bleached glaciofluvial facies. Ferruginous deposits were also found in the uppermost parts of non-glacial facies, such as the shallow marine Quwarah Member of the Qasim Formation and the braided deltaic Sajir Member of the Saq Formation. Compositionally, goethite was the dominant iron oxide mineral in all ferruginous deposits, and it is mostly distributed as cement, filling pore spaces. In comparison to ferruginous deposits reported in different depositional settings on Earth and Mars, the studied ferruginous deposits in an ancient glaciogenic setting exhibit different mineralogical characteristics. Specifically, the studied solid concretions are less abundant and primarily amalgamated, while the rinded concretions appear to be more mature than those reported in other depositional environments. This study suggests that the weathered basement rocks of the Arabian Shield were the primary source of iron. The iron-bearing rocks were eroded and transported by Hirnantian glaciation and deglaciation processes.